HYDRATION AND DEHYDRATION OF OCEANIC CRUST CONTROLS PB EVOLUTION IN THE MANTLE - Chauvel C.; Goldstein S.L.; Hofmann A.W. (My University, 1995)
The position of the Pb isotopic compositions of mid-ocean ridge basalts (MORB) to the right of the geochron has long puzzled geochemists. Uranium is more incompatible than Pb during mantle melting, and the mantle source of MORB, being depleted in incompatible elements, should have low Pb isotope ratios and plot to the left of the geochron. This has been called the ''lead paradox''. MORB have a second peculiar characteristic: Pb concentrations are drastically depleted relative to other elements of similar compatibility such as Ce or Nd. We suggest that both characteristics can be explained by preferential mobility of Pb during hydrothermal alteration of the oceanic crust associated with sea-floor spreading, and subsequent dehydration during subduction. A portion of this Pb migrates into the mantle wedge and is then added to the continental crust via arc magmas. Parts of the Pb-depleted recycled oceanic crust are stored at some deep level in the mantle and eventually become the source of ocean island basalts, the rest mixes into the mantle to become the MORB source. This model is evaluated quantitatively and special attention is given to the evolution of the Ce ratio in the depleted mantle from the beginning of Earth history to the present.